Initial management of lower urinary tract symptoms and bladder outlet obstruction. (September 2019) - Sahdev, Varun; Speakman, Mark J.
Abstract: Lower urinary tract symptoms (LUTS) affect >60% of men and women aged >40 years. Symptoms may be classified as storage, voiding or post-micturition and have a variety of systemic, neurological, drug-related or urological causes. There is growing evidence that obesity and metabolic syndrome are linked to LUTS. Initial evaluation of LUTS should follow a structured system, with symptom scores and frequency–volume charts. Several features have been identified as risk factors for progression of LUTS, and stratification using these factors can aid in planning management. For example, older age and a high-normal prostate-specific antigen can suggest a higher risk of progression to acute urinary retention. Many patients with LUTS require no treatment. If indicated, first-line treatment for LUTS should be conservative with lifestyle changes, and then medical therapy, involving selective α-adrenoceptor blockers, 5α-reductase inhibitors, antimuscarinics, mirabegron or a combination of these. Phosphodiesterase-5 inhibitors may also improve symptom scores and quality of life, and may become more routine in use for LUTS in the future.